2020
DOI: 10.3390/ijerph17124258
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship between Transport Interventions, Mode Choice, and Travel Perception: An Empirical Study in Beijing, China

Abstract: Transport interventions help to facilitate the sustainable travel behavior. The effects of transport interventions on travel choices have been addressed extensively. However, little research has been devoted to the influence of transport interventions and travel choice on travel perception. This study aimed to investigate the relationship among the three aspects. Two intervention measures, information intervention and public transport service improvement, were selected. Intervention experiments were designed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…There is an interaction between different modes of travel and travel perceptions. Fan [48] showed that bicyclists have a more positive impact on travelers, whereas public transportation is more likely to produce negative feelings such as fear of being late and having a sense of stress. The effect of age on broad travel satisfaction may be due to the stressful life of the traveler.…”
Section: Discussionmentioning
confidence: 99%
“…There is an interaction between different modes of travel and travel perceptions. Fan [48] showed that bicyclists have a more positive impact on travelers, whereas public transportation is more likely to produce negative feelings such as fear of being late and having a sense of stress. The effect of age on broad travel satisfaction may be due to the stressful life of the traveler.…”
Section: Discussionmentioning
confidence: 99%
“…Travel happiness reflects travellers' cognitive and affective evaluation of trips. Previous studies have demonstrated the significant impacts of travel happiness on travel choice behaviour [28,29]. In this study, travel happiness was included and measured based on the widely applied STS (Satisfaction with Travel Scale), which was proposed by Ettema et al [30].…”
Section: According To Statistics From the International Energymentioning
confidence: 99%
“…Similar observation was made in China, where public information campaigns to create awareness about pro-environmental travel behaviour helped in increasing the use of public transport and walking but did not have a sustainable longterm impact. This was attributed to the lack of knowledge about transport services, a prerequisite for change in behaviours [19].…”
Section: Mechanisms That Influenced Transportation Interventions In L...mentioning
confidence: 99%
“…In recent years, to cope with rapid urbanisation, a few initiatives towards improving access and safety in urban transport infrastructure have been undertaken for older adults in different low-and middle-income countries [15][16][17]. Despite efforts from national and international agencies to address the needs of older adults concerning public transportation (for e.g., bus rapid transit systems, bus corridors with priority lanes, improvement in public transport and non-motorised transport services) inequalities faced by older adults while accessing urban transport infrastructure are noticeable across regions [14,18,19]. Subsidised fare made public transport affordable to the most vulnerable population in Latin American countries such as Columbia and Chile [20].…”
Section: Introductionmentioning
confidence: 99%